About "Wolfgang Tillmans – four books" - Arçari, André (Revista do Colóquio, 2023)
This written review presents the publication “Four books” by German artist Wolfgang Tillmans, whose photographic work can be read as a reflection of the culture and life of generation X. This artist's production flourishes during a period of free movement between the states -members of the EU, where his career took off in the 1990s, given the German political opening after the fall of the wall, globalization and the importance of the subject's subjectivation processes. It was during this period that Tillmans collaborated on both fashion and continental photographs of techno and acid house for i-D and Purple, and was a witness to the impacts of AIDS on the queer community. Four Books stands out for bringing in a large volume the fragmentary way that makes up his research, a kind of puzzle where the constitution of meaning in images takes place in the process of subjectivization of objects, events and subjects, from and through transient materiality present in its surrounding world. Furthermore, this is his fifth book published by Taschen, in celebration of the publisher's 40th anniversary, where they are gathered in chronological order: Wolfgang Tilmans, 1995 / Burg, 1998 / Truth Study Center, 2005 / Neue Welt, 2012.